Pengaruh Profitabilitas, Kepemilikan Publik dan Kepemilikan Institusional Terhadap Nilai Perusahaan - Mega Atrimevia Ramadhani; Dade Nurdiniah (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
This study aims to examine and analyze the effect of profitability, public ownership and institutional ownership on firm value. This research uses quantitative methods. The population in this study are property, real estate and building construction companies listed on the Indonesia Stock Exchange (BEI) 2016-2018. Determination of the sample is done by purposive sampling technique and obtained a sample of 46 companies or 138 research data based on certain criteria. Data analysis method used in this study is multiple linear regression using IBM SPSS 25. The results of this study indicate that profitability has a positive and significant effect on firm value. While public ownership and institutional ownership do not affect the value of the company.